Reverberation, disembodied gesture, performance: The performative dimension of the word in public art (Palíndromo, 2021)
This paper proposes a theoretical approach of the performative dimension of the word in public art, articulating analytical frameworks around performance borrowed from the works of Turner, Féral and Zumthor. By bringing into perspective approaches from different fields of the humanities, namely anthropology, the performing arts and literature, the text seeks to make possible the description of its object of interest - words operated by artists in public spaces - as one of the expressions of performance in contemporary art. To do so, it presents and relates the notions of liminoid/protostructure (TURNER, 1982, 2013), theatricality and performative act (FÉRAL, 2015), and performancial situation (ZUMTHOR, 2014).
Keywords: Word in performance; Performance; Performative act; Liminoid; Performance space